Set Bersifat-Q Dalam Ruang Topologi - Md. Tap, Abu Osman (MATEMATIKA, 1993)
Kertas ini mengkaji sifat-Q yang merupakan kekalisan tukar tertib pengoperasi tutupan dan pedalaman dalam ruang topologi. Sifat-Q dikekalkan di bawah pengoperasi peluaran, homeomorfisa dan hasil darab. Katakunci: Sifat-Q; operasi peluaran; homeomorfisa; hasil darab This paper studies the property-Q in which the closure and the interior operators commute in the topological apaces. The property-Q is preserved under the exterior operator, homeomorphism and product. Keywords: Property-Q; exterior operator; homeomorphism; product